Financial Integration in the Context of the European Union - Damdinsuren, Ariunaa (Mongolian Journal of International Affairs, 2021)
As the world continues to see various facets of financial integration, the topic has sparked a great deal of discussions among policy makers and economists. The article analyzes benefits and risks of financial integration in the context of the European Union, which has facilitated global financial integration immensely by creating common currency among European Monetary Union countries and harmonizing regulations across the region. Upon examining main pros and cons of financial integration in detail, I conclude that financial integration can be beneficial in the longrun if corrective and preventive measures are enforced to curtail risks and threats it poses.